MENGUKUR KETEPATAN KUALITAS INFORMASI SISTEM TRACER DAN TRACKING JASA KURIR - sasa ani arnomo (Universitas Putera Batam, 2018)
With the development of e-commerce, the sale and purchase transaction more and more. The scope of e-commerce is very wide because internet access is spread all over the region. The development of e-commerce users is affecting business in the delivery of goods. To know the goods have been processed for delivery or not the courier service delivery of goods provide trace and tracking system. In this study will examine how the accuracy of the quality of information on trace systems and tracking as a service system that provides convenience to users and customers in knowing where the goods we send or receive. The research variables as the direction of measurement are Interest (importance), Clarity (clarity), Relevance (relevance), usefulness (usefulness). Research method by means of descriptive research that is method used to analyze data by way of describing or describing data that have been collected. The samples taken are batam city people who have or are using the system trace and tracking courier services. The purpose of research to know how the quality of information displayed so as to provide information assessment for the community.